2010
DOI: 10.1371/journal.pone.0012740
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variant in Complement C3 Gene Promoter and Genetic Susceptibility to Temporal Lobe Epilepsy and Febrile Seizures

Abstract: BackgroundHuman mesial temporal lobe epilepsies (MTLE) represent the most frequent form of partial epilepsies and are frequently preceded by febrile seizures (FS) in infancy and early childhood. Genetic associations of several complement genes including its central component C3 with disorders of the central nervous system, and the existence of C3 dysregulation in the epilepsies and in the MTLE particularly, make it the C3 gene a good candidate for human MTLE.Methodology/Principal FindingsA case-control associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Eleven complement analytes were selected for this study, guided by reference to previous studies of complement biomarkers in epilepsy which have described increased serum levels or gene expression of C3, C4, C1q, iC3b and terminal complement complex (TCC), and availability of reagents and in-house assays [23,24,26,28,30]. The concentrations of nine analytes: iC3b, C1q, C3, C4, Properdin, Factor B (FB), Factor H (FH), C1 inhibitor (C1inh), and TCC were measured using established in-house enzyme-linked immunosorbent assays (ELISA) ( Table 2).…”
Section: Immunoassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven complement analytes were selected for this study, guided by reference to previous studies of complement biomarkers in epilepsy which have described increased serum levels or gene expression of C3, C4, C1q, iC3b and terminal complement complex (TCC), and availability of reagents and in-house assays [23,24,26,28,30]. The concentrations of nine analytes: iC3b, C1q, C3, C4, Properdin, Factor B (FB), Factor H (FH), C1 inhibitor (C1inh), and TCC were measured using established in-house enzyme-linked immunosorbent assays (ELISA) ( Table 2).…”
Section: Immunoassaysmentioning
confidence: 99%
“…Complement activation in the CNS is increasingly recognised to be associated with exacerbation and progression of tissue injury in degenerative and inflammatory diseases [21,22]. Dysregulation of the complement system in epilepsy has been observed both in human and animal studies [23][24][25][26][27]. For example, sequential infusion of individual proteins of the membrane attack pathway (C5b6, C7, C8, and C9) into the hippocampus of awake, freely moving rats induced both behavioural and electrographic seizures as well as neurotoxicity, suggesting a direct role for the complement system in epileptogenesis [28].…”
Section: Introductionmentioning
confidence: 99%
“…The marker set was chosen to interrogate classical (C1q, iC3b, C3, C4), alternative (Properdin, FB, FH, iC3b) and terminal (TCC) activation pathways. Selected markers have been implicated in pathophysiology of mood disorders such as schizophrenia (Hakobyan et al, 2005;Mayilyan et al, 2008) and bipolar affective disorders (Akcan et al, 2017), and/or neurological and neurodegenerative disorders such as Alzheimer's disease (Kolev et al, 2009), Parkinson's disease (Loeffler et al, 2006), multiple sclerosis (Ingram et al, 2012) and epilepsy (Aronica et al, 2007;Jamali et al, 2010). CPR was measured because of its widely accepted use as a benchmark of inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies suggest that genetic susceptibility contributes to the development of seizure disorders (Cavalleri et al, 2007; Jamali et al 2010) and treatment response (Ebid 2007; Hung et al, 2005; Kwan et al, 2007), little has been studied in the area of genetic susceptibility to PTS. Previous work in our lab has shown that genetic variation in the adenosine A1 receptor is associated with susceptibility to PTS (Wagner et al 2010).…”
Section: 0 Introductionmentioning
confidence: 99%